Chirality induction on non-chiral dye-linked polysilsesquioxane in nanohelical structures. Issue 53 (8th June 2020) - Ryu, Naoya; Kawaguchi, Tsutomu; Yanagita, Hiroshi; Okazaki, Yutaka; Buffeteau, Thierry; Yoshida, Kyohei; Shirosaki, Tomohiro; Nagaoka, Shoji; Takafuji, Makoto; Ihara, Hirotaka; Oda, Reiko
Abstract : Chirally arranged organic dye-linked polysilsesquioxane was prepared, through a sol–gel transcription using its non-chiral precursor with a chiral supramolecular template, and its chiroptical properties were investigated. Abstract : We demonstrate the direct induction of chirally arranged organic dye-linked polysilsesquioxane through a sol–gel transcription using a chiral supramolecular template. The chiral arrangement was confirmed by using electronic and vibrational circular dichroism and circularly polarized luminescence spectroscopies.